Plasma technologies for manufacturing of micro-strip metal detectors of ionizing radiation - Pugatch, V.M.; Perevertaylo, V.L.; Fedorovich, O.A.; Borisenko, A.G.; Kostin, E.G.; Kruglenko, M.P.; Polozov, B.P.; Tarasenko, L.I. (Вопросы атомной науки и техники, 2007)
The manufacturing of elements of micro-strip metal detectors (MSMD) for ionizing radiation applying plasma-chemistry technologies for etching of multilayer structures is described in details. Results obtained by using plasma-chemistry technologies for MSMD production as well as its advantages in comparison with a wet chemical etching, problems arising and possible ways of their elimination are presented.